MENGATASI MISKONSEPSI SISWA PADA POKOK BAHASAN LINGKARAN DENGAN STRATEGI PEMBELAJARAN KONFLIK KOGNITIF - Erna Dewi Pangesti (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2017)
This research aim to describe misconception profile which is experienced by students of VIII-C SMPN 12 Madiun in 2016/2017 on the subject of the circle and its causal factors and to describe whether learning with cognitive conflict strategy can overcome misconceptions experienced by students. This research was descriptive qualitative research. The results of this research indicate that: (1) the misconception profile experienced by students is that students do not understand the definition of the circumference, so that when the students calculate the circumference of a field formed from the circle and restricted by two radius of the circle, the student only counts the circumference Section of the circle without adding lengths twice the radius of the circle. As students calculate the circumference of the circular and rectangular joints, the students calculate the circumference of parts of the circle and rectangles separately, and sum the results or students only count the circumference of parts of the circle only. Students are still difficult to change the story related to the wide circle into a mathematical sentence. (2) factors causing misconceptions experienced by students were students lack understanding of the definition of the circumference itself, the lack of business students in solving problems faced by mathematics, students do not repeat the material that has been taught, homework given not corrected and discussed, Teachers use only lecture methods that make students feel bored with math lessons (3) based on learning outcomes that cognitive conflict learning strategies can overcome misconceptions experienced by students.